The significance of cheese sampling in the determination of histamine concentration: Distribution pattern of histamine in ripened cheeses. (15th December 2022) - Moniente, Marta; García-Gonzalo, Diego; Llamas-Arriba, M. Goretti; Garate, Jone; Ontañón, Ignacio; Jaureguibeitia, Arrate; Virto, Raquel; Pagán, Rafael; Botello-Morte, Laura
Abstract: Cheeses are becoming a major safety and public health concern: cheeses available in supermarkets occasionally contain high histamine concentrations that can have negative effects on consumer health. In this study, we have attempted to assess the histamine distribution pattern in ripened cheeses, with the purpose of establishing a correct cheese sampling strategy for the quantification of histamine. To this aim, histamine was determined in four distinct areas of twelve long-ripened hard cheeses: the external and internal rind, along with the outer and inner core of the wedge. The concentrations measured were remarkably different: histamine accumulated in the central core, whereas the lowest amount was found in the peripheral rind. To explain this heterogenous distribution, histamine producers were determined in the four areas by identifying the hdc sequences obtained from cheese samples. Non-starter bacteria were identified as main histamine producers; however, these microbiota were homogeneously distributed throughout the wedge. Nevertheless, the analysis of psychochemical properties of the different areas revealed an observable trend: histamine tended to accumulate in the saltier, more humid, and less oxidized areas in a wedge. Overall, this study highlights the significance of a correct sampling strategy when histamine is quantified in cheese. Highlights: Ripened cheese showed a clear pattern of histamine distribution. Histamine accumulated in the central core, whereas the peripheral rind contained the lowest amount. A well-defined sampling strategy can improve histamine content measurement in ripened cheese. Histamine tended to accumulate in the saltier, more humid, and less oxidized areas in the wedge.